Clinicopathologic features and surgical treatment prognosis of esophageal carcinosarcoma - Shen, Jiangfeng; Lu, Kaijin; Liu, Fuxing; Chen, Xia; Chen, Quan; Wu, Bingbing; Wang, Hailan; Ge, Pengfei; Han, Guang; Wang, Fei; Zhang, Peng; Yin, Pei; et al. (Frontiers in Oncology, 2024)
Carcinosarcoma is a rare esophageal tumor, accounting for approximately 0.27-2.8% of malignant esophageal tumors. Out of the 1261 patients who underwent surgical treatment for esophageal cancer, 16 cases were pathologically confirmed as carcinosarcoma. Among them, two underwent neoadjuvant chemotherapy, six received postoperative chemotherapy, one underwent exclusive radiotherapy postoperatively, and two received a combination of postoperative chemotherapy and radiotherapy. Carcinosarcomas predominantly occurred in the middle (43.75%) and lower (50%) segments of the esophagus. Microscopic examination revealed coexistence and transitional transitions between sarcomatous and carcinoma components. Among the 16 patients, 15 (93.75%) were positive for vimentin, 11 (68.75%) for CKpan, 13 (81.25%) for CK5/6, and 13 (81.25%) for p53. Pathological staging showed 5 cases in stage T1, 2 in stage T2, and 9 in stage T3, with lymph node metastasis observed in 6 cases (37.5%). TNM staging revealed 3 cases in stage I, 9 in stage II, and 4 in stage III. The overall 1, 3, and 5-year survival rates were 86.67%, 62.5%, and 57.14%, respectively. Univariate analysis indicated that pathological N staging influenced survival rates, while multivariate analysis demonstrated that pathological N staging was an independent prognostic factor. Complete surgical